2004
DOI: 10.1158/0008-5472.can-04-1399
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated Akt3 Activity Promotes Development of Malignant Melanoma

Abstract: Malignant melanoma is the skin cancer with the most significant impact on man, carrying the highest risk of death from metastasis. Both incidence and mortality rates continue to rise each year, with no effective long-term treatment on the horizon. In part, this reflects lack of identification of critical genes involved and specific therapies targeted to correct these defects. We report that selective activation of the Akt3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
629
4
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 530 publications
(658 citation statements)
references
References 32 publications
17
629
4
8
Order By: Relevance
“…Although experiments in fibroblasts have implicated a role for PI-3 kinase/Akt signaling in the regulation of p27 Kip1 (Mirza et al, 2004), we have not observed alterations in p27 Kip1 levels upon treatment with the PI-3 kinase inhibitor, LY294002, in melanoma cell lines (data not shown). Nevertheless, the role of PI-3 kinase/Akt signaling in melanoma cell cycle events warrants further investigation as this pathway is frequently altered (Stahl et al, 2004). p27 Kip1 levels in melanoma cells are also regulated by the proteasome.…”
Section: Discussionmentioning
confidence: 99%
“…Although experiments in fibroblasts have implicated a role for PI-3 kinase/Akt signaling in the regulation of p27 Kip1 (Mirza et al, 2004), we have not observed alterations in p27 Kip1 levels upon treatment with the PI-3 kinase inhibitor, LY294002, in melanoma cell lines (data not shown). Nevertheless, the role of PI-3 kinase/Akt signaling in melanoma cell cycle events warrants further investigation as this pathway is frequently altered (Stahl et al, 2004). p27 Kip1 levels in melanoma cells are also regulated by the proteasome.…”
Section: Discussionmentioning
confidence: 99%
“…We predicted that IGF1R knock-down was inhibiting signaling via other pathways including PI3K-Akt that have a major influence on survival (Peruzzi et al, 1999). Indeed blockade of the PI3K-Akt pathway was shown to be capable of inducing apoptosis and inhibiting melanoma tumor development (Stahl et al, 2004). In CHL-1 cells transfected with empty vector or WT B-RAF, we observed a decrease in Akt phosphorylation two days post-transfection with IGF1R siRNA (Figure 4a).…”
Section: Igf1r Targeting In V600e B-raf Melanomamentioning
confidence: 90%
“…In addition, DNA copy gain involving the AKT3 locus has recently been described in melanoma, and selective AKT3 activation may characterize 40%-60% of sporadic tumors (Stahl et al 2004). However, the complexity of this signaling cascade has not been fully understood.…”
Section: Pten Negative Regulator Of Phosphatidylinositol 3-kinase (Pmentioning
confidence: 99%